Leishmaniases in Ethiopia: a scoping review protocol to determine the scope of research and remaining gaps - Ermias Diro; Katherine O'Brien; Mezgebu Silamsaw Asres; Richard Wamai; Hugh Shirley; Grace Grifferty; Eleni Ayele; Philip Espinola Coombs (BMJ Open)
Introduction The leishmaniases are among the group of neglected tropical diseases that cause significant morbidity and mortality each year. Currently, the East Africa region has the highest visceral leishmaniasis burden in the world. Ethiopia is one of the East African countries that reports both visceral and cutaneous forms of the disease. As part of the Nairobi Declaration, Ethiopia showed commitment to the elimination of visceral leishmaniasis by 2030. In this endeavour, it is important to understand the scope of research conducted on leishmaniases in the country and identify where the research gaps exist. Determining the research landscape is vital in the plan towards leishmaniases control and elimination. It will help to reference conducted research, determine if systematic reviews are warranted and help prioritise future research directions.Methods and analysis This protocol was developed with reference to the JBI Scoping Review Methodology Group’s guidance on conducting scoping reviews and the PRISMA-ScR reporting guidelines for scoping reviews. The following databases will be searched: PubMed, Embase via Embase.com, Web of Science Core Collection, Cochrane CENTRAL, Global Index Medicus, ClinicalTrials.gov, the Pan African Clinical Trials Registry and PROSPERO. Locally published literature that may not be indexed in the above-mentioned systems will be identified through team members familiar with the setting. Each record will be dually and blindly reviewed in an abstract-title screen and full-text screen using inclusion–exclusion criteria. Included articles must contain an in-depth discussion of leishmaniasis in Ethiopia. Data extracted will consist of study themes, study types, and categories and subcategories each defined in the developed codebook, in addition to type of leishmania, year of publication, funding source and the number of citations. Results will be reported with summary statistics.Ethics and dissemination Individual consenting and ethical approvals are not applicable. We plan to disseminate our findings to the appropriate stakeholders.